Dog culling and replacement in an area endemic for visceral leishmaniasis in Brazil - Nunes, Caris Maroni [UNESP]; Felix de Lima, Valeria Marcal [UNESP]; de Paula, Henrique Borges [UNESP]; Venturoli Perri, Silvia Helena [UNESP]; de Andrade, Andrea Maria; Ferreira Dias, Francisca Elda; Burattini, Marcelo Nascimento (Elsevier B.V., 2008)
Measures employed to control visceral leishmaniasis in Brazil have focused on vector control by residual insecticide spraying and diagnosis of infection with elimination of positive dogs. We describe dog culling and replacement in a Brazilian endemic area (the Alvorada District, Aracatuba, SP) in order to better understand dog population dynamics when elimination of the dog reservoir is adopted as the main control measure. From August 2002 to July 2004, 60.9% of the estimated dog population for the area was culled with a mean age of 34 months old. The presence of anti-Leishmania sp. antibodies was recorded for only 26.7% of the euthanized canines. Replacement was observed in 38.8% of the cases, some of them by 2 or more dogs and in a mean time of 4 months. Dogs were replaced mostly by puppies of both sexes with a mean age of 6.8 months. From August 2002 to April 2005 we were able to follow-up 116 of these dogs, during a mean time of 8.7 months. Canine visceral leishmaniasis seropositivity by ELISA was observed in 42.2% of the followed dogs, 30.6% of which were already positive at the first evaluation. By the end of the follow-up period 37% of the dogs were submitted to euthanasia, with a mean age of 18.3 months. In the studied CVL endemic area of Brazil, euthanasia and the subsequent replacement ratio were high, increasing the dog population turnover and leading to a younger population that might be more susceptible to a variety of other infectious diseases in addition to CVL. Dog culling as a control strategy for VL should be reassessed. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: canine visceral leishmaniasis; dog culling; dog replacement